The economic disturbance theory and the merger activity in Britain: An empirical investigation - A. Pouris (South African Journal of Business Management, 1985)
This article is an empirical exploration of the hypothesis, advanced by Gort (1969), that mergers are the result of disturbed expectations owing to economic and technological shocks. The importance of this theory lies in the fact that it attempts to explain the observed cyclic pattern of merger activity and to provide a link between the neoclassical set of explanations and the timing of mergers. The tests point out that changes in merger rates over time and among industries in Britain are not determined by changes in technology and/or stock prices. Residual contributions are the comprehensive discussion of the availability and sources of data on mergers and stock price indices in the United Kingdom, and an indication, with policy implications, that merger activity may affect the performance of the stock market adversely.
Keywords: 650